Gender stereotype and advertisement language on newspaper and magazine media platform in Nigeria - Omiunu, Ojinga Gideon (Journal of Print and Media Technology Research, 2023)
This study seeks to investigate gender stereotype and the language of advertising used in media platform in Nigeria. A convenient sampling was deployed to select three indigenous newspapers and two magazines in Nigeria. The three newspapers used for this study are the Tribune, Guardian and the Nation; and the two magazines used are Ovation and City people. The findings of the study revealed that gender bias occurs in media advertisement in Nigeria and it is more pronounced in newspaper than in the magazines. Body images of females in advertisement were more exposed that those of male and the most revealed female body parts were the arms, thigh and chest, among others, while for the males only their arms and legs were revealed. The majority of advertisement done in newspaper and magazines are gender specific, that is, they addressed particular and specific gender type thus neglecting the other gender type. The study recommends that the female gender should not be portrayed in the society as mere sex objects. Also, advertising agencies should endeavor to make advertisements to be gender neutral; however, it is also important to put into cognizance the particular gender for which the advertisement is produced.